1996
DOI: 10.7326/0003-4819-125-12-199612150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Vitamin D3Supplementation Prevents Bone Loss in the Spine Secondary to Low-Dose Corticosteroids in Patients with Rheumatoid Arthritis

Abstract: Calcium and vitamin D3 prevented loss of bone mineral density in the lumbar spine and trochanter in patients with rheumatoid arthritis who were treated with low-dose corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1
15

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(135 citation statements)
references
References 0 publications
4
115
1
15
Order By: Relevance
“…1 These recommendations are based on the safety profile of moderately dosed calcium and vitamin D and studies demonstrating that (1) oral glucocorticoids can lead to rapid bone loss within the first 3 months of glucocorticoid use, 2 and (2) while the risk of GIOP increases with the cumulative glucocorticoid dose, there is no dose of glucocorticoids that does not accelerate bone loss or increase fracture risk; 3,4 (3) several randomized controlled trials have shown that the administration of calcium and vitamin D in patients undergoing glucocorticoid therapy can prevent early bone loss. [5][6][7] In contrast, recommendations regarding the use of bisphosphonates are individualized based on risk factors and childbearing potential.…”
Section: Introductionmentioning
confidence: 99%
“…1 These recommendations are based on the safety profile of moderately dosed calcium and vitamin D and studies demonstrating that (1) oral glucocorticoids can lead to rapid bone loss within the first 3 months of glucocorticoid use, 2 and (2) while the risk of GIOP increases with the cumulative glucocorticoid dose, there is no dose of glucocorticoids that does not accelerate bone loss or increase fracture risk; 3,4 (3) several randomized controlled trials have shown that the administration of calcium and vitamin D in patients undergoing glucocorticoid therapy can prevent early bone loss. [5][6][7] In contrast, recommendations regarding the use of bisphosphonates are individualized based on risk factors and childbearing potential.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium and vitamin D supplementation have been shown to ameliorate bone loss 26 and bisphosphonates unarguably reduce bone loss and replenish bone once lost. 5,27 Other drugs such as calcitriol 28 and calcitonin 29 prove beneficial in some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…O uso combinado de cálcio e vitamina D parece ser melhor do que o uso isolado destas substâncias nos pacientes com osteoporose induzida por corticosteróides, com ganho diferencial de massa óssea de 3,2% (40) . Em pacientes portadores de artrite reumatóide e em uso de corticosteróides, a combinação do uso de cálcio 1,0 grama diária, mais 500 UI de vitamina D3 levou a um aumento da densidade mineral óssea na coluna lombar de 0,72% ao ano, comparado a uma perda de 2% por ano no grupo placebo (41) . O uso da combinação de cálcio com vitamina D não parece suficiente para prevenção da perda de massa óssea nos pacientes com artrite reumatóide, quando estes estão sob regime de tratamento com doses elevadas de corticosteróides por tempo prolongado (42) .…”
Section: Erosões óSseas Subcondraisunclassified